A Comparative Legal Analysis of Military Insubordination: Perspectives from National Law and Islamic Criminal Law - Dede Kurniawan; Ramadani (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2025)
Military criminal offenses represent violations of hierarchical discipline, a foundational principle of the military system. This research examines the legal analysis of insubordination committed by military personnel from the perspective of Islamic criminal law. The primary objective of this study is to evaluate how the legal system—both positive law and Islamic criminal law—assesses the crime of insubordination within the military context. This study employs a qualitative normative juridical methodology, using a statute and conceptual approach to examine relevant legal provisions, including military criminal codes and Islamic jurisprudential sources. The findings reveal that insubordination is classified under Article 106 of the Indonesian Military Criminal Code (KUHPM) as a serious offense involving disobedience or resistance toward a superior officer. From the perspective of Islamic criminal law, such conduct is closely associated with jarīmat al-baghyu (rebellion) and is punishable under the category of ta‘zīr, which allows for discretionary sanctions such as imprisonment, dismissal, or other corrective measures. This study offers original insight by bridging the gap between formal military legal systems and Islamic legal thought, emphasizing the role of moral and ethical values in reinforcing military discipline. The implications suggest the potential for integrating ta‘zīr-based principles into Indonesia’s military justice system to enhance internal discipline through a framework grounded in justice, piety, and legal authority.